Spław wiślany w 1662 roku (w świetle rejestru celnego komory nowodworskiej) - Kazusek, Szymon (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
W artykule omówiony został spław wiślany w 1662 r. na podstawie jedynego zachowanego rejestru komory celnej na Wiśle z drugiej połowy XVII w. Przedstawiona analiza sezonowości żeglugi wiślanej dowiodła, że znany z literatury spław z tzw. pierwszą wodą nie odgrywał kluczowej roli w handlu. Zależał on istotnie od pory letnich i jesiennych deszczów w żegludze z nurtem rzeki, a także od rytmu potrzeb konsumenckich. Dowiedziono zależności pomiędzy wielkością transportu wodnego a kategorią społeczną uczestnika spławu oraz porą sezonu żeglugowego. Wykazano dominujący udział szlachty w spławie z nurtem Wisły oraz mieszczan w spławie w górę rzeki. Opisano strukturę taboru wodnego, a także preferencje w zakresie jego wykorzystania, w tym także w zależności od pory roku kalendarzowego. Przedstawiono strukturę własności jednostek pływających, zwracając uwagę na dominację szlachty. Podkreślono rolę Warszawy i innych, w tym nadwiślańskich, miast w handlu spławnym. Scharakteryzowano pełną strukturę spławianych towarów, a także środowisko uczestników spławu, dostrzeżono rolę dopływów Wisły w handlu spławnym. Porównując badane zjawisko ze spławem w latach 1605–1651 oraz w 1766 r., dowiedziono wyjątkowego znaczenia handlu wiślanego tuż po potopie szwedzkim.

The article discusses Vistula rafting in 1662 on the basis of the only surviving register of a customs house on the Vistula, dating from the second half of the 17th century. The presented analysis of the seasonality of the Vistula shipping proved that rafting with the so-called first water, as it was known from in literary circles, did not play a key role in trade. Instead, navigation of the river current primarily depended on the summer and autumn rains, as well as on the rhythms of consumer needs. The relationship between the size of water transport and the social category of the rafting participant as well as the time of the shipping season is also highlighted. It is also shown that the majority of the downriver traffic was nobility while the upstream traffic was mainly townspeople. The structure of the water fleet was established, as well as its preferred use, which was also dependant on the season. The ownership structure of the vessels is discussed, paying attention to the dominance of the nobility. The role of Warsaw and other cities, including those on the Vistula River, in nautical trade is discussed. A comprehensive description of the transported goods was presented, as well as the environment of raft occupants, the role of the Vistula tributaries in floating trade was noticed. Comparing rafting in the years 1605-1651 and in 1766, the exceptional significance of the Vistula trade just after the Swedish Deluge was proved.
Vistula rafting in 1662 (in the light of the customs register of the Nowy Dwór chamber)
Keywords: spław wiślany; żegluga śródlądowa; handel; XVII wiek; kupcy; Rzeczpospolita; Wisła; rafting on the Vistula; inland sailing; trade; 17th century; merchants; Polish Commonwealth; Vistula